An Error Analysis of Writing Products Made By Indonesian Islamic University Students - Suhono Suhono; Bambang Yudi Cahyono; Falentinus Ndruru (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
The mismatch between the grammar used in writing English and the structure of Indonesian was often the leading cause of errors in writing. This article further analyzed the error analysis of writing products made by Indonesian Islamic university students of EFL More specifically, this study attempted to describe the types of grammatical errors in written products, the frequent types of grammatical errors, and the students’ awareness of errors. Two methods, quantitative and qualitative, were applied to accomplish this. Written tests and semi-structured interviews were used to collect the data. Students’ written Production was analyzed for errors based on the Surface Strategy Taxonomy Theory proposed by Dulay, Burt, and Krashen. The findings of this study revealed that students from Indonesian Islamic universities displayed a range of errors in their written products. The most prevalent errors identified were Misformation errors within the writing products of these EFL students. The errors committed by the students in their written outputs were further substantiated by the results of interviews, indicating that, whether aware or unaware, the students struggled to recognize and self-correct their grammatical errors in their written product. This study has provided significant insights into teaching English in general and specifically in writing instruction. By understanding the types of sentence errors commonly made by students, educators can focus on critical teaching points and effectively monitor their student’s adherence to the lessons delivered.